Constraints and Enablers to Growth of Female-Owned Businesses: Empirical Review - Hieu Minh VU; Chijioke NWACHUKWU (Communications of International Proceedings, 2020)
Globally, there is a growing interest in female entrepreneurship. many female-owned businesses are faced with several obstacles that threaten their survival and growth. this paper focuses on literature in women entrepreneurship contexts. considering recent events, it is important to understand the enablers and the constraints female entrepreneurs experience in a developing country context.  we draw insights about the subject using historical data and findings from past studies. based on our review, it was observed that gender discrimination, financial constraints, work-family conflict, lack of infrastructural support, unfavorable business and political environments, lack of entrepreneurship education, and personality-related issues hinders growth, profitability, and cause the failure of female-owned businesses. furthermore, creative education and training, leveraging team attributes and resources, digital technology, the nature of the industry, type of financing, and women entrepreneur empowerment stimulate the growth of female entrepreneurship. The authors conclude that policymakers must create a conducive environment and incentives to promote female entrepreneurship.
Keywords: Female Entrepreneurship; Feminist Theory; Institutional Theory; Enablers; Constraints